Dynamic optical tweezers: Experiment - Mitatha, S.; Noppanakeepong, S.; Ali, J.; Yupapin, P. P. (My University, 2010)
We have experimentally generated the optical tweezers in the form of a dark soliton pulse using the Stimulated Brillouin Scattering (SBS) system. This is the first time ever found on the use of the highly intense pulse in the form of a dark soliton to perform the dynamic light trapping probe known as a "dynamic optical tweezers". The advantage of the generated tweezers is that it can be used to transmit and transport the trapping atom/molecule into the optical device and communication network, which can be claimed as the dynamic optical tweezers transportation, for used in many frontier applications. The multi-optical tweezers generated, with high capacity regime can then be used for multi-optical tweezers transmission. The various applications to form the frontier research using photon, atom, molecule, DNA, electron and ion trapping for atomic tools, tiny synchrotron, molecular networks, bottom up atom/molecule assembly, ozone repair etc. are described. The experimental details and model of the optical tweezers generation and related characteristics are described. The interesting simulation results of a dark soliton generation for the optical tweezers are also analyzed and discussed in various applications. ©2010 IEEE.